Assessment of the biomass hydrolysis potential in bacterial isolates from a volcanic environment: biosynthesis of the corresponding activities - P.M. Stathopoulou; A.P. Galanopoulou; G.E. Anasontzis; Karagouni, A.D.; D.G. Hatzinikolaou (World Journal of Microbiology and Biotechnology, 2012)
The biomass degrading enzymatic potential of 101 thermophilic bacterial strains isolated from a volcanic environment (Santorini, Aegean Sea, Greece) was assessed. 80 % of the strains showed xylanolytic activity in Congo Red plates, while only eight could simultaneously hydrolyze cellulose. Fifteen isolates were selected on the basis of their increased enzyme production, the majority of which was identified as Geobacilli through 16S rDNA analysis. In addition, the enzymatic profile was evaluated in liquid cultures using various carbon sources, a procedure that revealed lack of correlation on xylanase levels between the two cultivation modes and the inability of solid CMC cultures to fully unravel the cellulose degrading potential of the isolates. Strain SP24, showing more than 99 % 16S DNA similarity with Geobacillus sp. was further studied for its unique ability to simultaneously exhibit cellulase, xylanase, β-glucosidase and β-xylosidase activities. The first two enzymes were produced mainly extracellularly, while the β-glycosidic activities were primarily detected in the cytosol. Maximum enzyme production by this strain was attained using a combination of wheat bran and xylan in the growth medium. Bioreactor cultures showed that aeration was necessary for both enhanced growth and enzyme production. Aeration had a strong positive effect on cellulase production while it negatively affected expression of β-glucosidase. Xylanase and β-xylosidase production was practically unaffected by aeration levels.